New Insights on the Conversion Reaction Mechanism in Metal Oxide Electrodes for Sodium-Ion Batteries - Mosa, Jadra (Nanomaterials (Basel), 2021)
Due to the abundance and low cost of exchanged metal, sodium-ion batteries have attracted increasing research attention for the massive energy storage associated with renewable energy sources. Nickel oxide (NiO) thin films have been prepared by magnetron sputtering (MS) deposition under an oblique angle configuration (OAD) and used as electrodes for Na-ion batteries. A systematic chemical, structural and electrochemical analysis of this electrode has been carried out. The electrochemical characterization by galvanostatic charge–discharge cycling and cyclic voltammetry has revealed a certain loss of performance after the initial cycling of the battery. The conversion reaction of NiO with sodium ions during the discharge process to generate sodium oxide and Ni metal has been confirmed by X-ray photoelectron spectra (XPS) and micro-Raman analysis. Likewise, it has been determined that the charging process is not totally reversible, causing a reduction in battery capacity.